2017
DOI: 10.1007/s00253-017-8238-0
|View full text |Cite
|
Sign up to set email alerts
|

High lactic acid and fructose production via Mn2+-mediated conversion of inulin by Lactobacillus paracasei

Abstract: Lactobacillus paracasei DSM 23505 is able to produce high amounts of lactic acid (LA) by simultaneous saccharification and fermentation (SSF) of inulin. Aiming to obtain the highest possible amounts of LA and fructose, the present study is devoted to evaluate the impact of bivalent metal ions on the process of inulin conversion. It was shown that Mn strongly increases the activity of the purified key enzyme β-fructosidase. In vivo, batch fermentation kinetics revealed that the high Mn concentrations accelerate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…In contrast to the complex and partially redundant starch-degrading enzymes in Bacteriodetes , fructans degraders carried fewer fructanases. Fructan utilization is not conserved within members of a specific species [ 41 , 42 , 70 ]. Three GH32 enzymes, including BT1760 (extracellular), BT3082 (periplasmic), and BT1765 (intracellular), as well as hybrid two-component (HTC) signaling system, BT1754 are required for fructan utilization in B .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to the complex and partially redundant starch-degrading enzymes in Bacteriodetes , fructans degraders carried fewer fructanases. Fructan utilization is not conserved within members of a specific species [ 41 , 42 , 70 ]. Three GH32 enzymes, including BT1760 (extracellular), BT3082 (periplasmic), and BT1765 (intracellular), as well as hybrid two-component (HTC) signaling system, BT1754 are required for fructan utilization in B .…”
Section: Discussionmentioning
confidence: 99%
“…GH68 family enzymes in lactobacilli are extracellular levansucrases which are necessary for biofilm formation on non-secretary epithelia of the upper GI tract; these enzymes synthesize levan but do not contribute to fructan hydrolysis [ 71 ]. Intracellular GH32 β-fructofuranosidases of lactobacilli (ScrB) utilize only di- and trisaccharides that are transported across the membrane [ 36 , 70 , 72 ]. The metagenomic analysis is the first to report the presence of extracellular fructanases (FruA) in intestinal lactobacilli.…”
Section: Discussionmentioning
confidence: 99%
“…Lactobacillus paracasei can produce large amounts of lactic acid through simultaneous sacchari cation and fermentation of inulin. Studies have shown that high concentrations of Mn 2+ accelerate the hydrolysis of inulin by increasing the activity of β-fructosidase, and increasing the conversion of sugar to lactic acid by increasing the overall glycolytic ux (Petrov et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…We also observed a striking effect regarding the LacI family. Two members were 4.76-and 3.73-fold downregulated in 8-1, the central catabolite regulator CcpA in several genera of LAB [64,65] and a repressor of the maltose operon, respectively. Another member from the same family, the evolved β-galactosidase operon repressor EbgR, was 2.51-fold upregulated in Ym1.…”
Section: Transcription Factors and Regulatorsmentioning
confidence: 99%